Allowing Undocumented Immigrants to Obtain Driver's Licenses in New Mexico: Revising, Not Abandoning, the System - Steven J. Escobar (Washington University Journal of Law & Policy, 2014)
Although Gov. Martinez has yet to successfully repeal the 2003 Amendments, the question of whether or not to allow undocumented immigrants to obtain driver's licenses has dominated New Mexico state politics since the passage of HB 173, and it has entered the national spotlight as immigration has become a hot-button issue in recent years. The national attention given to the debate over whether to repeal HB 173 led to the composition of this Note. The outcome of this debate, as well as the successes and failures of HB 173, could influence immigration policy in New Mexico and other states for years to come. If HB 173 is deemed a success, and the 2003 Amendments are not revoked, more states might adopt similar policies. In contrast, if issues of fraud are not appropriately addressed, other states might be less likely to follow New Mexico's lead. Part II of this Note begins with the history of HB 173 and the policies supporting its passage. This is followed by an overview of the arguments made by both supporters and opponents of HB 173 on the bill's effect on New Mexico. These arguments include concerns about fraud, Gov. Martinez's attempts to have the 2003 Amendments repealed, New Mexico's temporary residency verification program, and Arizona's passage of Senate Bill 1070 (SB 1070), as well as the effect of SB 1070 on the number of driver's licenses issued to undocumented immigrants in New Mexico. This overview transitions into a discussion of the current status of the debate over HB 173 in New Mexico. Following the historical examination, Part III critically analyzes the effect of HB 173. This analysis is followed by Part IV, in which several proposals are set forth for resolving the issue in a manner that balances the interests of all parties involved.
Keywords: undocumented immigrants; new mexico; undocumented immigrants in new mexico; driver' s licenses